ANALISIS FAKTOR YANG MEMPENGARUHI NILAI EKONOMIS GARAM. (STUDI KASUS DI KECAMATAN TLANAKAN KABUPATEN PAMEKASAN) - Runik Puji Rahayu; Rohmaniyah Rohmaniyah (Al-Amien Prenduan for Islamic Institute, 2022)
This study aims to determine the factors that affect the economic value of salt and to determine the effect of fluctuations in the economic value of salt on the welfare of salt farmers. This research is a qualitative research, namely research that is used to determine the economic value of salt that occurs in the Tlanakan, Pamekasan. The population in this study were all members of salt farmers. The sample used in this study was 8 members. The data analysis technique in this study uses a process of systematically searching and compiling data obtained from interviews, field notes, and documentation. The conclusion of this study shows that imports are the biggest influence on local salt prices, consequently if imports continue, local salt cannot reach the price desired by farmers in meeting the needs and desires of their families.